Gulls as vectors for plastics and nutrient transport across natural aquatic environments - Martín-Vélez, Víctor; Sánchez, Marta I.; Cañuelo Jurado, María Belén; Céspedes, Vanessa; Cózar, Andrés; Ros, Macarena; Navarro, Joan; Afán, Isabel; Forero, Manuela G.; Green, Andy J. (Sociedad Ibérica de Ecología, 2022)
2nd Meeting of the Iberian Ecological Society (SIBECOL), 3-8 July 2022, Aveiro, Portugal Interest in plastic contamination in inland aquatic environments due to human activity has been growing greatly. The amount of plastic produced generates severe environmental problems, due to long term deposition, but also because plastic breaks down into smaller pieces that persist and interact with aquatic biota. Many waterbirds (e.g. gulls) have shifted their natural behaviour to exploit constant anthropogenic resources (e.g. rubbish dumps) and may be biovectors of plastics and nutrients between terrestrial and aquatic environments. In south-west Spain Lesser black backed gull (Larus fuscus) and yellow legged gull (Larus michahellis) are opportunistic species exploiting resources at dumps and biovectoring plastics to natural environments (e.g. at Fuente de Piedra Lagoon and Odiel marshlands respectively) through pellet and faecal deposition. However, the role of gulls as plastic vectors has not been quantified so far. Using movement data acquired with GPS devices, combined with censuses and analysis of pellets and faeces collected from the wetlands, we quantify the amounts of plastics, other debris, and nutrients imported by gulls into these two internationally important wetlands. We consider possible management measures to reduce the extent of these biovectoring processes Peer reviewed